A Novel Approach on Tech Solutions to Mitigate Big Data Security Threats - Suneetha, V; Sunitha, M; Arshiya, Arshiya (International Journal of Computer Sciences and Engineering, 2025)
Big Data is the buzz word today. Numerous projects centering big data are booming. It hides in itself vital information which if unearthed would provide great insights into various areas. The growing need of this data is complicating security. Handling big data projects is a challenging task. To prevent a potentially disastrous data breach, big data security should be considered seriously. To prevent security issues, some simple steps should be implemented. It can be done with best practices and internal controls, like protecting against NoSQL Injection points. These points provide a way for attackers to access Big Data. This paper discusses the various big data security threats and different innovative Tech solutions to meet many of the security concerns hindering the Big Data persistence, analysis and presentation.